2009
DOI: 10.1007/s11431-009-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

Toughness and characterization of reactive powder concrete with ultra-high strength

Abstract: A number of three-point bending and fracture tests of 200 MPa-level reactive powder concrete (RPC) with the various fiber contents have been conducted to probe the nature and characteristics of toughness of RPC200. The contribution of the embedded fibers to improving the crack-resistant capacity, energy absorption capacity and toughness with various deformation mechanisms has been analyzed. Taking account of that the first-crack deformation, peak-load deformation and their improvement varied with the fiber con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The linear expansion coefficient  f is 10×10 6 /°C  f 12×10 6 /°C [3,109], which is less than that of the matrix of RPC  l 0 (see Table 2). Therefore, the apparent linear expansion coefficient  l  of the fiber-reinforced RPC decreases with increasing fiber content.…”
Section: Physical Mechanism Of Variation Of Thermal Expansion Coefficmentioning
confidence: 90%
See 1 more Smart Citation
“…The linear expansion coefficient  f is 10×10 6 /°C  f 12×10 6 /°C [3,109], which is less than that of the matrix of RPC  l 0 (see Table 2). Therefore, the apparent linear expansion coefficient  l  of the fiber-reinforced RPC decreases with increasing fiber content.…”
Section: Physical Mechanism Of Variation Of Thermal Expansion Coefficmentioning
confidence: 90%
“…(21) and (9), it is shown that theoretical equations are considerably similar to the empirical equations based on regression analysis of the experimental data. The elastic modulus and the elastic wave velocity c of fiber-reinforced RPC increase with increasing fiber volumetric fraction  v [3], which leads to the increase of the Debye temperature (see eq. (17)).…”
Section: Physical Mechanism Of Variation Of Specific Heat Capacitymentioning
confidence: 99%
“…It remarkably impairs the uniformity of stress-strain response of brittle and concrete-like materials and greatly lowers the precision and reliability of experiment results [37][38][39][40][41]. According to the observed static mechanical properties of RPC [3,7], a copper plate with diameter of 20 mm and thickness of 2.5 mm was mounted to the head of the incident bar as a wave shaper to extend the impulse rising time and reduce both the dispersion effect of incident wave and the inertial effect.…”
Section: Impact Tests and Measurementsmentioning
confidence: 99%
“…With specific fabrication procedures, RPC achieved a static compressive strength between 200 and 800 MPa, a flexural strength around 140 MPa and a rupture energy capacity as much as 40 kJ/m 2 . RPC can sustain 500°C high temperature for two hours with a residual strength of 50% of the peak compressive capacity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For these exclusive physical and mechanical performances, RPC has been widely promoted and applied in construction of highways, bridges, skyscrapers, oversized buildings, nuclear facilities, military engineering, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since the advent of RPC, it has attracted great attention for both academic and engineering aspects and has been widely used in a variety of engineering applications, such as skyscrapers, pavements, bridges, runways, nuclear containments, underground tunnels, etc. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%